UPAYA MENINGKATKAN HASIL BELAJAR PSIKOMOTORIK MATERI MERODA PADA PEMBELAJARAN SENAM LANTAI DENGAN PENDEKATAN PEMBELAJARAN BERDIFERENSIASI DI KELAS VIII SMPN 2 SEMARANG - Kartiko Wibowo, Unggul; Kresnapati, Pandu; Juwahir, Juwahir (Journal of Physical Activity and Sports (JPAS), 2024)
This research is based on when students do cartwheels they are still not optimal so that in practice students still have difficulty and have not mastered the technique well. Apart from that, in learning there are still students who have not optimized their learning time as well as possible, they don't pay much attention to the teacher and tend to get bored. In this study, the researcher aims to improve learning outcomes in floor exercise activities on cartwheels using a differentiation learning approach. This research is classroom action research (PTK) which took place in 2 cycles with 2 meetings. The research subjects were 33 class VIII students at SMPN 2 Semarang. Data collection techniques using observation of learning and skills. In cycle I, the percentage of students reached 54.5% who had completed the KKM and 45.4% who had not completed the KKM. In cycle II there was an increase in the category of having completed the KKM as many as 27 students or 84.9% and 5 students or 15.1%. Based on the research results, it can be concluded that using a differentiated learning approach in learning cartwheels on floor exercise activities for class VIII students at SMPN 2 Semarang can improve student learning outcomes.